Let F ( x ) = f ( x ) + f ( x 1 ) , where f ( x ) = ∫ 1 x 1 + t lo g t d t .
Then F ( e ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Observe that the substitution t = 1 / u leads us to
f ( x 1 ) = ∫ 1 x 1 t + 1 lo g t d t = ∫ 1 x u 1 + 1 lo g ( 1 / u ) ( u 2 − 1 ) d u = u → t ∫ 1 x t ( t + 1 ) lo g t d t ,
and therefore
F ( x ) = f ( x ) + f ( x 1 ) = ∫ 1 x ( ( t + 1 ) lo g t + t ( t + 1 ) lo g t ) d t = ∫ 1 x t lo g t d t .
Here integration by parts will show us that
F ( x ) = 2 lo g 2 x ,
and therefore F ( e ) = 1 / 2 .
Problem Loading...
Note Loading...
Set Loading...
f ( x ) ⟹ f ( x 1 ) = ∫ 1 x 1 + t lo g t d t = ∫ 0 lo g x 1 + e u u e u d u = ∫ 0 lo g x 1 1 + e u u e u d u = ∫ 0 − lo g x 1 + e u u e u d u = ∫ 0 lo g x 1 + e − v v e − v d v = ∫ 0 lo g x e v + 1 v d v Let t = e u ⟹ d t = e u d u Let u = − v ⟹ d u = − d v Multiply up and down by e v
Therefore,
F ( x ) ⟹ F ( e ) = f ( x ) + f ( x 1 ) = ∫ 0 lo g x 1 + e u u e u d u + ∫ 0 lo g x 1 + e u u d u = ∫ 0 lo g x u d u = 2 lo g 2 x = 2 lo g 2 e = 2 1